Effects of Aerobic Capacity Phenotype on Adaptive Responses to Ischemic Stress - Fontenot, Elizabeth Gail (East Carolina University, 2009)
Ischemic disease leads to increased tissue stress by decreasing supply of nutrients adequate to meet energy demands. To maintain functionality, compensatory mechanisms for diminished vascular supply are induced by numerous tissues factors associated with ischemia. Compensatory responses include both remodeling of the vascular network to sustain substrate delivery and adaptive responses within affected tissue to sustain function despite diminished substrate availability. Active aerobic exercise has been shown to improve both vascular and metabolic remodeling within and around ischemic tissues. However, active exercise programs, while consistently beneficial, still generate a very heterogeneous response, suggesting the potential for an important contribution from the genetic composition determining intrinsic aerobic exercise capacity. A novel rat strain, developed using forced artificial selection for intrinsic endurance running capacity, provides a unique tool that enables assessment of intrinsic aerobic capacity and the effects of these phenotypes on adaptive responses to ischemic stress. Untrained low endurance running capacity (LCR) rats were found to have a higher incidence of risk factors for ischemic disease and may have differing vascular and metabolic responses to peripheral artery occlusion. The overall goal of this dissertation was to determine the influence of intrinsic exercise capacity on the vascular and metabolic adaptive responses to ischemic stress. This study tested the hypothesis that the LCR would show altered vascular and metabolic adaptive responses in response to peripheral arterial occlusion, compared to HCR counterparts. Muscle samples from both the ischemic and the non-ischemic limb in both strains were compared metabolically for their relative capacity to oxidize fatty acid, histologically for the anatomical vascular capillarity supporting perfusion, and functionally using both perfusion tracers to track blood flow, and direct muscle stimulation to test fatigue characteristics. Biomarkers obtained using PCR were obtained to suggest potential pathways accounting for differences in response between the phenotypes. Results indicate that intrinsic aerobic phenotype does alter both the resting tolerance for demand induced ischemia, as well as the adaptive compensatory responses to chronic anatomic arterial obstruction. The LCRs showed both a reduced capacity for demand induced workloads, as well as responses to chronic obstruction that were both delayed in onset, and delayed in induction compared to HCR counterparts. These data may have implications for better structuring active exercise programs to achieve intended outcomes in limiting consequences associated with cardiovascular disease risk factors.
Keywords: Biology, Physiology; Aerobic capacity; High capacity running rats; Ischemic disease; Low capacity running rats; Models, Animal; Biology; Physiology